Efektivitas Kebijakan Hukum Pidana dalam Menjamin Perlindungan Hak Asasi Manusia terhadap Korban Perdagangan Orang di Indonesia - Jesslyn Elisandra Harefa; Suci Ramadani; Muhammad Arif Sahlepi (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The rapid development of information technology has opened up opportunities for new threats to national security, one of which is information system hacking. Cyberattacks not only cause economic losses and disrupt public services but also pose a serious threat to Indonesia's digital sovereignty. In this context, state intelligence plays a strategic role as the vanguard in detecting, analyzing, and countering various threats to the country's strategic information systems. However, strengthening the state intelligence function in countering hacking crimes still faces various obstacles, ranging from immature regulations, weak inter-agency coordination, to limited technology and human resources. This study aims to assess the effectiveness of strengthening state intelligence in countering information system hacking and to formulate the urgency of updating national legal policy to support the formation of a strong, integrated, and professional cyber intelligence system. Using normative legal research methods supported by conceptual and case-based approaches, this study concludes that strengthening state intelligence requires regulatory updates, institutional integration, and investment in technology and human resources to safeguard national sovereignty in the digital era.